The seven minute screen: a neurocognitive screening test highly sensitive to various types of dementia - Meulen, E (BMJ Group, 2004)
Background: The seven minute screen (7MS) is a compilation of the temporal orientation test, enhanced cued recall, clock drawing, and verbal fluency. It has been shown to be useful for detecting Alzheimer's disease in a population of patients with memory complaints. Objective: To assess the predictive validity of the 7MS for various types of dementia, and the influence of depression and other psychiatric conditions on 7MS scores. Setting: Multicentre: secondary referral sites across the Netherlands. Subjects: 542 patients with various types of dementia or depression, together with 45 healthy controls. Results: Alzheimer's disease was diagnosed in 177 patients, other types of dementia in 164. The sensitivity of the 7MS for Alzheimer's disease was 92.9% with a specificity of 93.5%. For other types of dementia the sensitivity was 89.4% and the specificity 93.5%. Cognitive abnormalities were found in 71% of the patients with depression (n = 31). The mean (SD) duration of administration of the 7MS was 12.4 (4.6) minutes, range 8 to 22, depending on dementia severity. Conclusions: The 7MS is a useful screening tool for discriminating patients with dementia from cognitively intact patients. This not only applies to Alzheimer's disease but also to other types of dementia. Specificity with respect to depression was lower for the 7MS than for the MMSE.